The Rhetorical Design of Darkness: Reading Implicatures in Frost. - Gilbert, Stephen W (Sincronía, 2026)
This article offers a rhetorical and pragmatic reading of Robert Frost’s poem “Design” (1922), focusing on the implicatures generated by the rhetorical questions in the final sestet. Moving beyond dominant thematic interpretations—particularly those related to the argument from design and theodicy—the author shifts attention to the stylistic and discursive mechanisms that shape readers’ ethical and religious judgments. Drawing on H. P. Grice’s theory of implicature and its development by Sperber and Wilson, the study analyzes how Frost constructs a rhetorical progression that gradually introduces notions of agency and dark design in nature. The analysis shows that the early questions generate relatively weak implicatures associated with anomaly, while later questions intensify causal attribution, culminating in the phrase “design of darkness to appall.” The article argues that certain interpretations—such as attributing rhetorical intent to darkness—emerge as weak implicatures, for which readers themselves bear responsibility. Thus, the poem’s final ambiguity does not resolve the problem of design but instead invites readers to assume an ethical and hermeneutic responsibility in interpretation. The article concludes that the punctuation and syntax of the final couplet are deliberate rhetorical devices that preserve the tension between determinism and contingency, reinforcing the ethical dimension of reading.